The Habit Alimentaires Analysis (Food Habit) of Hypoatherina sp. Larvae in East Pelawangan Segara Anakan Cilacap - Subiyanto Subiyanto; Herimawan M.F.; Siti Rudiyanti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2008)
Observations about kind of food in the Hypoatherina sp. side arrested in East Pelawangan Segara Anakan Cilacap. Food habits of observation methods conducted by the method according to the number of Effendie, (1997) 6). Based on the analysis of Hypoatherina sp. larvae food habits and analysis of plankton found in the study showed that the stomach contents of larval size 3,1-5,0 mm or at the beginning of taking food from other species in common with the abundant natural food in the waters, where the largest constituent Bacillariophyceae class. Along with its growth, there is a change in food habits 5,1-7,0 mm long dominated by the food standards Bacillariophyceae (27.5%) and Ciliophora (24.4%). 7,1-9,0 mm long while the standard changed to Bacillariophyceae (19.4%) and Copepod (25.9%). 9,1-11,0 mm, and in turn again to the Copepod (39%) and Cyanophyta (34%). From this research can be concluded that the Hypoatherina sp. is a type of plankton-eating fish, both types of phyto and zooplankton. Key words : Food habit, Fish larvae, Plankton